Value-Added of Sweet Orange Peel Waste into TiO2 Nanoparticles via Green Synthesis for Antibacterial Applications - Woradech Meedech; Natchayaporn Sakulpeeb; Sutee Chutipaijit; Wantana Koetniyom; Supamas Wirunchit (Thai Journal of Nanoscience and Nanotechnology, 2025)
This research focuses on the TiO2nanoparticles synthesized via a green chemistry approach using extracts from sweet orange (Citrus sinensis) peels. The quality of the synthesized titanium dioxide nanoparticles was enhanced through an annealing process at 350°C for 6 hours. It was found that this thermal treatment significantly improved the particle quality. The antibacterial activity of the nanoparticles was investigated at concentrations of 0.1, 0.3, and 0.5 mg/mL in deionized water using the disc diffusion technique against both Gram-positive and Gram-negative bacteria. Staphylococcus aureus (S. aureus)and Escherichia coli (E. coli)were used as representative strains for Gram-positive and Gram-negative bacteria, respectively. The results indicated that the TiO2at a concentration of 0.5 mg/mL exhibited the most effective antibacterial performance against both types of bacteria.
Keywords: Nanoparticles: synthesis and applications; TiO2 Photocatalysis and Solar Cells; Water and Wastewater Treatment